OPTIMIZATION OF LAND USE IN ACCORDANCE WITH THE GENERAL EKOLOGICAL CRITERIA IN CONTAMINATED. - Kuzyn N.V. (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2017)
In the paper all the main positive and negative factors in particular the rational use and protection of land are analyzed. The system of common environmental criteria optimization of land use in terms of radiation contamination is presented. The order and sequence of application of common environmental criteria of optimal land use in terms of radiation contamination are determined. Rational use and protection of land large scientific-technical, social, economic, and environmental issue of our time, the solution of which depends achieve both economic and social goals of our society. This is primarily due to the exceptional role of land in the production of wealth, constraint, and the inability to replace land resources and anthropogenic environmental changes in large areas, causing activation of soil erosion, creating man-made landscapes, flooding, and flooding large areas of land pollution products and waste industrial production, radionuclides, chemicals. The feature of the land is also not the same quality and fertility of different plots, property continuously improved when used properly. The Chernobyl disaster a substantial part of the territory of Ukraine dangerous radiation situation, about 20% of the long term are the basis for the manifestation of small doses of radiation is created. This necessitates the analysis of areas of land for their suitability for agricultural production. Significant impact on agricultural production in many regions of Ukraine were consequences of the Chernobyl disaster. Thus, about 20% of Ukraine have a long-term basis for the display of small doses of radiation. Research methods of organizational systems, environmental, economic, and technological measures to ensure stable functioning of agro-ecosystems based radiation factor is carried out. In research still missing environmental and economic analysis of the relationship between the efficiency of land use and economic-economic factors, but some parts of this communication were studied in various aspects of individual experts (both soil scientists, surveyors, and economists). However, some previously developed land and security measures are based only on the results of fragmentary (in key areas) and the component (mostly soil and geo-botanical) studies. This approach to basic research in the field of sustainable land use, particularly in terms of radiation contamination, does not sound scientific foundations placement agricultural and industrial production, study land protection measures, is not conducive to the stability of the environment. Analyzing the system of generally defined environmental criteria optimization of land use should be noted that they are essential and should be used in the analysis of land use in terms of radiation contamination. It should only determine the order and sequence of their calculation. This will create a coherent methodology for optimizing land use in terms of radiation contamination. The order of calculation of main criteria defined on the PC provides:- Calculation of radionuclide transfer from soil to plants, taking into account the density of pollution.- Determination of eligibility agro-industrial groups of soils for growing crops, depending on the density of pollution.- Determining the fate of contamination of agricultural products relative to the control level, depending on the density of pollution.- Calculation washout of soils. A definite order and sequence of generally defined environmental criteria the optimum use of land in terms of radiation contamination allows to analyze the status of land use and recommendations for further land use. Methodological foundations are based on the current economic and mathematical methods and the use of electronic computer engineering, advanced research in the field of radiology, ecology, land use and so on.